International trade and the occupational mix in manufacturing: Evidence from german micro data - Dominik Boddin; Philipp Henze (Kiel University, Department of Economics, 2015)
We use the Establishment History Panel from 1975 to 2010 provided by the German Federal Employment Office to examine the impact of international trade on the occupational structure of the German manufacturing sector. To capture trade, we match the Establishment History Panel with UN Comtrade trade data. To do so, we develop a new matching approach that takes the input and output structure of the German manufacturing sector into account. We identify three different trade channels: import intensity, import competition, and export intensity. Using a fixed-effects Poisson regression model, we find diverse occupational effects from trade at the industry-level, while establishment-level estimations show only few significant effects.
Keywords: J21; F16; F61; L23; 330; International Trade; Occupational Mix; Firm Organization